Antarctic stratospheric ice crystals - Goodman, J.; Toon, O. B.; Pueschel, R. F.; Snetsinger, K. G.; Verma, S. (1989)
Ice crystals were replicated over the Palmer Peninsula at approximately 72 deg S on six occasions during the 1987 Airboirne Antarctic Ozone Experiment. The sampling altitude was between 12.5 and 18.5 km (45-65 thousand ft pressure altitude) with the temperature between 190 and 201 K. The atmosphere was subsaturated with respect to ice in all cases. The collected crystals were predominantly solid and hollow columns. The largest crystals were sampled at lower altitudes where the potential temperature was below 400 K. While the crystals were larger than anticipated, their low concentration results in a total surface area that is less than one tenth of the total aerosol surface area. The large ice crystals may play an important role in the observed stratospheric dehydration processes through sedimentation. Evidence of scavenging of submicron particles further suggests that the ice crystals may be effective in the removal of stratospheric chemicals.